Mössbauer effect in the eight-iron ferredoxin from Clostridium pasteurianum. Evidence for the state of the iron atoms - C. L. Thompson; C. E. Johnson; D.P.E. Dickson; Richard Cammack; D.O. Hall; Ulrich Weser; Krishna Rao (1974)
1. Mössbauer spectra of both redox states of the eight-iron ferredoxin from Clostridium pasteurianum were observed over a range of temperatures and in magnetic fields. 2. At high temperatures (77 degrees K and above) the spectra of both states consist essentially of the superposition of two or more closely similar doublets. 3. The average chemical shift for the oxidized protein leads to the proposal that each of the two four-iron active centres consists formally of two Fe(3+) and two Fe(2+) atoms. 4. The average chemical shift and quadrupole splitting increase on reduction, consistent with there being one Fe(3+) and three Fe(2+) atoms per centre in the reduced molecule. 5. The spectral changes on reduction show that all the iron atoms are affected when one electron is added to each four-iron centre. 6. No separate Fe(3+) and Fe(2+) spectra were observed (as they were, for instance, in the reduced two-iron plant ferredoxins) suggesting that the d electrons are not localized on particular atoms, but are shared approximately equally by all four atoms in the four-iron centres. 7. At low temperatures (4 degrees K and below) no magnetic hyperfine interaction was observed in the oxidized protein even in an applied magnetic field, confirming the non-magnetic nature of the molecule in the oxidized state, and suggesting that the four iron atoms in each centre are antiferromagnetically coupled together to give zero spin. 8. Magnetic hyperfine interaction was observed in the reduced protein at low temperatures, and showed that all the iron atoms were magnetic. This demonstrates that one electron goes to each centre on reduction. 9. On application of a large magnetic field to the reduced protein at low temperatures, both positive and negative hyperfine fields were shown to be present, thus directly showing that antiferromagnetic coupling exists between the iron atoms in the reduced state.